The Immune Factors Involved in the Pathogenesis, Diagnosis, and Treatment of Sjogren's Syndrome - Yi-fan Huang; Qian Cheng; Chun-miao Jiang; Shu An; Lan Xiao; Yong-chao Gou; Wen-jing Yu; Lei Lei; Qian-ming Chen; Yating Wang; Jun Wang (Clinical and Developmental Immunology)
Sjogren's syndrome (SS) is a systemic, autoimmune disorder characterized by salivary insufficiency and lymphocytic infiltration of the exocrine glands. Even though the mechanism of its pathology and progression has been researched ever since its discovery, the roles of different parts of immune system remain inconclusive. There is no straightforward and simple theory for the pathogenesis and diagnosis of Sjogren’s syndrome because of the multiple kinds and functions of autoantibodies, changing proportion of different T-lymphocyte subsets with the progression of disease, unsuspected abilities of B lymphocytes discovered recently, crosstalk between cytokines connecting the factors mentioned previously, and genetic predisposition that contributes to the initiation of this disease. On the other hand, the number of significant reports and open-label studies of B-cell depletion therapy showing clinical efficacy in sjogren’s syndrome has continued to accumulate, which provides a promising future for the patients. In a word, further elucidation of the role of different components of the immune system will open avenues for better diagnosis and treatment of SS, whose current management is still mainly supportive.